DESCRIPTION OF NEW FINANCIAL FRAUD AND MONEY LAUNDERING SCHEMES DURING THE WAR IN UKRAINE - Koibichuk, Vitaliia; Kochnieva, Valeriia; Buriak, Anna; Petrushenko, Yaroslav; Yehorova, Yuliia (Socio-economic relations in the digital society, 2024)
This article explores the emergence and evolution of financial fraud and money laundering schemes in Ukraine during the war. The study uses qualitative analysis methods, including a systematic review of news reports, scientific papers, and publicly available data. The findings reveal significant growth in financial fraud activities following the start of the full-scale invasion of Ukraine, driven by economic instability, emotional vulnerability, and trust in charitable initiatives. Key fraudulent schemes are categorized and analyzed, including volunteer fraud, fake investment projects, charity fraud, sales fraud, and banking and card scams. Furthermore, the study examines new fraudulent tactics, such as targeting government aid programs, impersonating social service representatives, and exploiting the psychological distress of victims. The research highlights how fraudsters quickly adapt to new circumstances during the war, creating increasingly sophisticated schemes to fraud individuals, military personnel, and organizations. Practical recommendations are provided for the prevention, detection, and mitigation of financial fraud in war contexts. These include enhancing public awareness, strengthening cybersecurity measures, improving legal frameworks, and fostering international cooperation to address the transnational nature of financial crimes. The study underscores the need for coordinated efforts between governmental structures, law enforcement agencies, and financial institutions to combat the rapidly evolving threat of financial fraud and money laundering during the war.
Keywords: financial fraud; money laundering; war; fraud; cybersecurity; full-scale invasion; Ukraine